EVALUASI PROGRAM FLOOD MANAGEMENT IN SELECTED RIVER BASINS DI KABUPATEN PANDEGLANG - Nugroho, Arif; Hakim, Agus Lukman; Handoko, Pryo; Sanjaya, Natta; Mulyani, Ipah; Hadiono, Ade (Jurnal Inovasi Daerah, 2023)
The problem of flooding and erosion is a natural phenomenon that greatly affects the community. Losses resulting from these events can reduce the quality of human life in various aspects of life. So there is a need for immediate management with various strategies. One of them is the Evaluation of the Flood Management in Selected River Basins Program in Pandeglang Regency. The purpose of this study was to evaluate the Farmland Management and Sustainable Agriculture Practices for Flood Management in Selected River Basins program Sector Project Pandeglang with the perspective of the CIPP evaluation model (Context, Input, Process, Product) and to recommend sustainability strategies. The research was conducted using a descriptive method with a qualitative approach. The results showed that the existence of the FMSRB program was able to answer various problems with critical lands and flood risk. Then the most effective continuation strategy that must be carried out is carried out by the Pandeglang Regency government with a Collaborative Governance strategy, namely collaboration between the Regency government and the private sector, universities/academics, and so on. The conclusion of the research is that the CIPP evaluation model can answer the main causes of flooding in the Pandeglang Regency.